2016
DOI: 10.1007/s10549-016-3734-y
|View full text |Cite
|
Sign up to set email alerts
|

The clinical value of HER-2 overexpression and PIK3CA mutations in the older breast cancer population: a FOCUS study analysis

Abstract: Studies to confirm the effect of acknowledged prognostic markers in older breast cancer patients are scarce. The aim of this study was to evaluate the prognostic value of HER-2 overexpression and PIK3CA mutations in older breast cancer patients. Female breast cancer patients aged 65 years or older, diagnosed between 1997 and 2004 in a geographical region in The Netherlands, with an invasive, non-metastatic tumour and tumour material available, were included in the study. The primary endpoint was relapse-free p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 52 publications
0
14
0
1
Order By: Relevance
“…These mutation frequencies may be underestimated. One possible reason is that most studies detected several exons with hotspot mutations via Sanger sequencing, spectrometry genotyping, or hydrolysis probe assays [4-13]. In the BOLERO-2 trial, tumor samples from 302 patients were analyzed via next-generation sequencing (NGS).…”
Section: Introductionmentioning
confidence: 99%
“…These mutation frequencies may be underestimated. One possible reason is that most studies detected several exons with hotspot mutations via Sanger sequencing, spectrometry genotyping, or hydrolysis probe assays [4-13]. In the BOLERO-2 trial, tumor samples from 302 patients were analyzed via next-generation sequencing (NGS).…”
Section: Introductionmentioning
confidence: 99%
“…The association between PIK3CA mutations and HER2-positive breast cancer is still unclear, as previous studies have related PIK3CA mutations with unfavorable clinical outcomes [7811161719], favorable outcomes [18], or found no significant impact [121314152021]. Many studies that concluded that PIK3CA mutations corresponded with poor clinical outcomes found lower pCR rates in the mutant group than in the wild-type group [78111719], and in some cases, the difference was more pronounced in the ER-positive group [719].…”
Section: Discussionmentioning
confidence: 99%
“…Although the frequency of the mutation varies according to molecular subtype, this mutation has been described in approximately 12% to 39% of human epidermal growth factor receptor 2 (HER2)-positive breast cancers [345678]. The PIK3CA mutation is being examined as a causative candidate for trastuzumab resistance in HER2-positive breast cancer due to the relevance of the PI3K/AKT pathway and HER2 [1910]; however, previous studies have been inconclusive [781112131415161718192021].…”
Section: Introductionmentioning
confidence: 99%
“…Трастузумаб и пертузумаб, моноклональные антитела против Her2 рекомендованы для большинства пациентов с Her2 + РМЖ, при этом комбинация трастузумаба, пертузумаба и таксанов указана в качестве предпочтительного режима терапии первой линии для лечения Her2 + метастатического РМЖ [20]. Обнаружено, что используемый маркер Her2 также является серьезным прогностическим фактором рецидива у более пожилых пациенток с РМЖ [31], что сопоставимо с результатами исследований у более молодых пациентов. Анализы NCCN в рамках программы SEER-Medicare говорят о том, что пожилые пациенты, приступив к лечению по схемам с трастузумабом, с меньшей вероятностью, чем молодые женщины, способны завершить 1 год терапии [9,10].…”
Section: обзоры литературыunclassified